2011
DOI: 10.2174/138920111795470949
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Molecule Counting for Single-Molecule Studies in Crowded Environment of Living Cells without and with Broken Ergodicity

Abstract: We present a new approach to distinguish between non-ergodic and ergodic behavior. Performing ensemble averaging in a subpopulation of individual molecules leads to a mean value that can be similar to the mean value obtained in an ergodic system. The averaging is carried out by minimizing the variation between the sum of the temporal averaged mean square deviation of the simulated data with respect to the logarithmic scaling behavior of the subpopulation. For this reason, we first introduce a kind of Continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…However, those measurements and theory only considered a single "dynamic" exponent [30][31][32][33][34]. For the first time, we have developed the theoretical formulation and an FCS-based method in order to separate the spatial subdiffusion from temporal subdiffusion [1,2]. We have observed that FCS is superior at calculating spatially and temporally variable diffusion coefficients and our stimulated and experimental data support this.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, those measurements and theory only considered a single "dynamic" exponent [30][31][32][33][34]. For the first time, we have developed the theoretical formulation and an FCS-based method in order to separate the spatial subdiffusion from temporal subdiffusion [1,2]. We have observed that FCS is superior at calculating spatially and temporally variable diffusion coefficients and our stimulated and experimental data support this.…”
Section: Introductionmentioning
confidence: 62%
“…As opposed to normal translational diffusion, in which the movement of molecules is not correlated with their previous position, anomalous translational diffusion molecules are spatially and temporally correlated [1][2][3]. This spatio-temporal correlation reflects a fundamentally different behavior compared with the one in dilute or very dilute solution which, for example, affects the spread of molecules within live cells.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The origin of such kind of diffusion can be either a crowded environment as in cells [9], [2] or the result of a continuous time random walks [24]. However, the spatial diffusion is still formulated using ordinary differentiation.…”
Section: Fractional Diffusion and Normal Adsorptionmentioning
confidence: 99%
“…The subject became recently again of interest when the ideas of Delahay were used in Monte Carol simulations by Seri-Levy and Avnir [25] and generalized to a fractional formulation by Giona and Giustiniani [12] applied to fractal surfaces. In the field of nano-technology nano rods as catalyst were examined by Kwon et al [15], Such et al [29] experimentally examined diffusion and adsorption of single molecules on the KBr(001) surfaces and for bio-chemical applications like anomalous diffusion in crowded environments see [19], [9]. For recent applications on the nano scale see the compilation of Quirke [22].…”
Section: Introductionmentioning
confidence: 99%